The Strategy of Development Cluster SMES of Apples Dodol by Integration K-Means Clustering and Analytical Hierarchy Process Method - Siti Asmaul Mustaniroh; Mohammad Ala; Usman Effendi (e-2477-1929)
The purpose of this research is to determine the grouping of SMEs apple dodol in Batu and to determine an appropriate development strategy for each cluster. The method of grouping using K-means clustering which is integrated with the Analytical Hierarchy Process (AHP) method to determine the priority of the development strategy for each cluster. Variables used in grouping include the production capacity per month (X1), long of operation (X2), investment value (X3), the average sales revenue per month (X4), the amount of assets of SMEs (X5) and number of labor (X6). Factors to determine the development strategies are industry cluster, government also related and supporting industries. The number of sample for SMEs apple dodol consisted of five units. The result showed formed 2 clusters of SMEs apple dodol are created by k-means clustering method. The result of AHP method indicates the priority of development strategy for SMEs dodol apples, in cluster 1 is improving the quality and standardization of product and cluster 2 is increasing marketing access.